IMAGINE A COMMUNITY OF CAPOEIRA IN AFRICAN DIASPORA. (Fiep Bulletin - online, 2013)
In the modern history of Western civilization colonization of the system calls made by the dominant nations is a process of prioritization and socio-cultural arbitrariness, which resulted in a stratification and classification of companies "civilized". This concept of civilization is based on a hegemonic common reference to the period of the eighteenth century XVI, who represented the ideology which reflects the Eurocentric version colonizing of knowledge, especially in relração with the colonized peoples in the production of knowledge worthy of a junior, as in the example the African Diaspora. This study characterized themselves as bibliographical study, examining the socio cultural aspects of the fight / game Capoeira. From that context Capoeira to reconfigure itself, and is reinvented Brazil, with the entry of the berimbau, new scams, the emergence of new groups and procedures for game / fight, new methods of teaching, saying new identities, and building Identities of resistance , A redefining of the roles of black people in Brazilian society, getting to the point that it turns into Brazilian Intangible Heritage.